SISTEM INFORMASI ADMINISTRASI PENGELOLAAN BOS DI SDN SENDANG KULON MENGGUNAKAN METODE LANGSUNG - Ahmad Ashifuddin Aqham; Siti Istirokhah; Haris Ihsanil Huda (Lembaga Pengembangan Kinerja Dosen, 2022)
The school operational fund or BOS itself is a government program to provide funding for non-personnel costs for primary and secondary education units as a means of implementing the 9-year compulsory education program. The BOS program aims to free all types of education costs for all public and private elementary, junior high school students in Indonesia from school operational costs. SD N 2 Sendangkulon is a public elementary school located on Jalan Dk Kacang Kidul Rt 01 Rw 03 Sendangkulon Village, Kangkung District, Kendal Regency. SD N 2 Sendagkulon was founded in 1982 until now. The problem that is still being experienced by the BOS Management Team at SDN 2 Sendangkulon is that there is no administrative information system for processing BOS funds that is relevant to the needs of SDN 2 Sendangkulon, resulting in the lack of participation and involvement of all education stakeholders at SDN 2 Sendangkulon. The lack of teacher participation is due to the absence of teacher access rights to obtain information regarding the BOS budget. This is the basis for the importance of designing an administrative information system for processing BOS funds that is relevant and accurate to assist in the management of School BOS funds, because information disclosure is one of the keys to implementing the principles of transparency and accountability related to BOS funds. Another problem that occurred at SDN 2 Sendangkulon was in the process of making reports and being responsible for the management and use of BOS funds. The BOS treasurer experienced difficulties because there were frequent changes in the reporting format for BOS funds, especially if the treasurer was new.Based on the background and some of the problems above, the authors conducted a study entitled